Single-cell RNA sequencing reveals a peripheral landscape of immune cells in Schistosomiasis japonica - Junhui Li; Yu Zhang; Hao Li; Jie Jiang; Chen Guo; Zhaoqin Zhou; Yulin Luo; Chen Zhou; Yingzi Ming (Parasites & Vectors, 2023)
Abstract Background Schistosomiasis, also known as bilharzia, is a devastating parasitic disease. This progressive and debilitating helminth disease is often associated with poverty and can lead to chronic poor health. Despite ongoing research, there is currently no effective vaccine for schistosomiasis, and praziquantel remains the only available treatment option. According to the progression of schistosomiasis, infections caused by schistosomes are classified into three distinct clinical phases: acute, chronic and advanced schistosomiasis. However, the underlying immune mechanism involved in the progression of schistosomiasis remains poorly understood. Methods We employed single-cell RNA sequencing (scRNA-seq) to profile the immune landscape of Schistosomiasis japonica infection based on peripheral blood mononuclear cells (PBMCs) from a healthy control group (n = 4), chronic schistosomiasis group (n = 4) and advanced schistosomiasis group (n = 2). Results Of 89,896 cells, 24 major cell clusters were ultimately included in our analysis. Neutrophils and NK/T cells accounted for the major proportion in the chronic group and the healthy group, and monocytes dominated in the advanced group. A preliminary study showed that NKT cells were increased in patients with schistosomiasis and that CXCR2 + NKT cells were proinflammatory cells. Plasma cells also accounted for a large proportion of B cells in the advanced group. MHC molecules in monocytes were notably lower in the advanced group than in the chronic group or the healthy control group. However, monocytes in the advanced group exhibited high expression of FOLR3 and CCR2. Conclusions Overall, this study enhances our understanding of the immune mechanisms involved in schistosomiasis. It provides a transcriptional atlas of peripheral immune cells that may contribute to elimination of the disease. This preliminary study suggests that the increased presence of CCR2 + monocyte and CXCR2 + NKT cells might participate in the progression of schistosomiasis. Graphical Abstract